Synthesis and evaluation of modified chalcone based p53 stabilizing agents. Issue 17 (1st September 2017) - Iftikhar, Sunniya; Khan, Sardraz; Bilal, Aishah; Manzoor, Safia; Abdullah, Muhammad; Emwas, Abdel-Hamid; Sioud, Salim; Gao, Xin; Chotana, Ghayoor Abbas; Faisal, Amir; Saleem, Rahman Shah Zaib
Graphical abstract: Abstract: Tumor suppressor protein p53 induces cell cycle arrest and apoptotic cell death in response to various cellular stresses thereby preventing cancer development. Activation and stabilization of p53 through small organic molecules is, therefore, an attractive approach for the treatment of cancers retaining wild-type p53. In this context, a series of nineteen chalcones with various substitution patterns of functional groups including chloro, fluoro, methoxy, nitro, benzyloxy, 4-methyl benzyloxy was prepared using Claisen-Schmidt condensation. The compounds were characterized using NMR, HRMS, IR and melting points. Evaluation of synthesized compounds against human colorectal (HCT116) and breast (CAL-51) cancer cell lines revealed potent antiproliferative activities. Nine compounds displayed GI50 values in the low micromolar to submicromolar range; for example ( E )-1-phenyl-3-(3, 4, 5-trimethoxyphenyl)prop-2-en-1-one (SSE14108 ) showed GI50 of 0.473 ± 0.043 µM against HCT116 cells. Further analysis of these compounds revealed that ( E )-3-(4-chlorophenyl)-1-phenylprop-2-en-1-one (SSE14105 ) and ( E )-3-(4-methoxyphenyl)-1-phenylprop-2-en-1-one (SSE14106 ) caused rapid (4 and 8-h post-treatment) accumulation of p53 in HCT116 cells similar to its induction by positive control, Nutlin-3. Such activities were absent in 3-(4-methoxyphenyl)propiophenone (SSE14106H2 ) demonstrating the importance of conjugated ketone for antiproliferative and p53 stabilizing activity of the chalcones. We further evaluated p53 levels in the presence of cycloheximide (CHX) and the results showed that the p53 stabilization was regulated at post-translational level through blockage of its degradation. These chalcones can, therefore, act as fragment leads for further structure optimization to obtain more potent p53 stabilizing agents with enhanced anti-proliferative activities.